Study of high–low KPFM on a pn-patterned Si surface. (11th January 2022) - Izumi, Ryo; Li, Yan Jun; Naitoh, Yoshitaka; Sugawara, Yasuhiro
Abstract: Comparative measurements between frequency modulation Kelvin probe force microscopy (FM-KPFM) using low frequency bias voltage and heterodyne FM-KPFM using high frequency bias voltage were performed on the surface potential measurement. A silicon substrate patterned with p- and n-type impurities was used as a quantitative sample. The multi-pass scanning method in the measurements of FM-KPFM and heterodyne FM-KPFM was used to eliminate the effect of the tip–sample distance dependence. The measured surface potentials become lower in the order of the p-type region, n-type region and n + -type region by both FM-KPFM and heterodyne FM-KPFM, which are in good agreement with the order of the work functions of the pn-patterned Si sample. We observed the difference in the surface potentials due to the surface band bending measured by FM-KPFM and heterodyne FM-KPFM. The difference is due to the fact that the charge transfer between the surface and bulk levels may or may not respond to AC bias voltage.